Exploring brain tourism discourse in the tourism and hospitality sector: reawakening research in neurotourism - Emeka Ndaguba; Cina Van Zyl (Tourism and Hospitality Management)
Purpose – This study aims to conduct a thorough and systematic evaluation of the literature in tourism and hospitality to explore the latest advancements and innovative technologies that are reshaping personalized services within the realm of neurotourism. Methodology/Design/Approach - Data for this research was mined, using www.dimensions.ai, and analyzed using computer software called Citespace. Findings – The research established a paucity of neurotourism research in tourism and demonstrated that several challenges including cost and expertise make it difficult to address arising literature on mindfulness tourism. Originality of the research – the integration of neuromarketing, brain research, and neuroscience has the potential to revolutionize tourism marketing by introducing personalized approaches to services and products, overcoming the limitations of traditional market research in understanding human decision-making within the tourism industry. The integration of neuroscientific methods provides a paradigm shift in tourism marketing, enabling marketers to create personalized and emotionally resonant experiences. This shift extends beyond traditional methods, offering a deeper understanding of tourist behavior and desires. In conclusion, the ability to personalize experiences, leverage VR technologies, and adapt in real-time to changing preferences positions brain research is a key driver for the future of tourism marketing.